The results of the research on theory of the scarification hard-seed by oblique impact (Journal of Applied Science and Engineering A, 2024)
If rate higher than 20% of seed of perennial plants for fodder have hard shell that restrict water, moisture and air, in order to ensure swelling of the seed, and regular sprouting as a result of air, water and moisture through hard shell, it is required to use one of four methods such as method of water and moisture-heating, chemical, electrical, physical and mechanical. The mechanic method is based on breaking hard shell by friction and stroke impact and creating fissure. The research is aimed to research on process of obtuse breaking. In doing so, as tangential of pre and post-friction speed is higher, the more works is made against friction force and breaking is occurred more. We determined a formula express this difference, analyzed the process and reflection angle of the best breaking.  ln obtuse impact, we determined a formula to determine ratio between normal and tangential factor of the impacting force using law of movement force and quantity, and determined the highest reflection angle of tangential force of friction in collusion impact. As a result of mechanic impact, seed may be crushed. Therefore, we identified crushing and damage of the seed, factors of efficient breaking of the seed shell.